Disagreement Among Forecasters in G7 Countries - Dovern, Jonas; Fritsche, Ulrich; Slacalek, Jiri (The Review of Economics and Statistics, 2012)
We investigate determinants of disagreement—cross-sectional dispersion of individual forecasts—about key economic indicators. Disagreement about economic activity, in particular about GDP growth, has a distinct dynamic from disagreement about prices: inflation and interest rates. Disagreement about GDP growth intensifies strongly during recessions. Disagreement about prices rises with their level, declines under independent central banks, and both its level and its sensitivity to macroeconomic variables are larger in countries where central banks became independent only around the mid-1990s. Our findings suggest that credible monetary policy contributes to anchoring of expectations about inflation and interest rates. Disagreement for both groups of indicators increases with uncertainty about the actual series.